2019
DOI: 10.1111/clr.13435
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of static vs. dynamic computer‐assisted implant surgery in single tooth space: A randomized controlled trial

Abstract: Objectives The aim of this RCT was to compare the accuracy of implant placement between static and dynamic computer‐assisted implant surgery (CAIS) systems in single tooth space. Materials and methods A total of 60 patients in need of a single implant were randomly assigned to two CAIS groups (Static n = 30, Dynamic n = 30) and implants were placed by one surgeon. Preoperative CBCT was transferred to implant planning software to plan the optimal implant position. Implants were placed using either stereolithogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
131
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 28 publications
9
131
4
3
Order By: Relevance
“…All parameters from both groups were in a range of likely values when compared to the previous studies. 7,11,[16][17][18][19] Moreover, the deviations observed in this study were smaller than those reported in in vitro studies, such as the study by Ruppin et al 20 on three different CAIS systems, who reported mean platform deviation of less than 1.5 mm and mean angular deviation of less than were 8.1 in partially and fully edentulous human cadaver mandibles. Similarly, Somogyi-Gnass et al 21 reported mean deviations static and dynamic CAIS at platform and apex less than 1.91 and 1.14 mm, respectively, and mean angular deviation less than 4.2 , with no significant differences to be found.…”
Section: Computer-assisted Implant Planningmentioning
confidence: 52%
See 2 more Smart Citations
“…All parameters from both groups were in a range of likely values when compared to the previous studies. 7,11,[16][17][18][19] Moreover, the deviations observed in this study were smaller than those reported in in vitro studies, such as the study by Ruppin et al 20 on three different CAIS systems, who reported mean platform deviation of less than 1.5 mm and mean angular deviation of less than were 8.1 in partially and fully edentulous human cadaver mandibles. Similarly, Somogyi-Gnass et al 21 reported mean deviations static and dynamic CAIS at platform and apex less than 1.91 and 1.14 mm, respectively, and mean angular deviation less than 4.2 , with no significant differences to be found.…”
Section: Computer-assisted Implant Planningmentioning
confidence: 52%
“…4,5 Then the virtually planned implant position is transferred to the real surgical sites by means of a custom-made guided surgery template in the case of static CAIS or through a real-time tracking and guidance of the surgical drill in dynamic CAIS systems. [6][7][8] Both static and dynamic CAIS systems come with different potential and limitations, although they are both based on a virtually planned optimal implant position. Static CAIS systems would not allow the surgeon direct visual contact with the working surgical site and intraoperative change from the planned position is difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) During surgery, the surgical plan and the size of the implant can be changed according to the actual clinical situation. (3) The surgeon can improve their accuracy and reduce surgical damage by being able to react instantly to the positional distance between the drill and the anatomical structure [22]. However, the disadvantages of dental navigation systems include the following: (1) Expensive equipment is required.…”
Section: Introductionmentioning
confidence: 99%
“…[ 53 ] On comparing static and dynamic guided approach, studies done by Kaewsiri et al . [ 54 ] and Mischkowski et al . [ 55 ] explained dynamic navigation, provided higher accuracy than the static guide system.…”
Section: Considering the Realitymentioning
confidence: 99%